ANALISIS PENGELOLAAN ARSIP DINAMIS AKTIF BAGIAN SEKRETARIAT DINAS PETERNAKAN PROVINSI JAWA TIMUR - Febrianti, Talqimusholihah; Utami, Dian Arlupi (Universitas Negeri Surabaya, 2025)
This research is motivated by the importance of managing active dynamic archives in supporting the smooth running of government administration. The high demand for managing created records is not matched by the availability of storage space for active and inactive records, as well as the limited number of professionals with dedication and competence in the field of archiving. This condition is the main urgency in this research, as it can disrupt the smooth running of administration and weaken information control within the agency. The purpose of this study is to analyze the management of active dynamic archives in the Secretariat of the East Java Provincial Livestock Service based on four focuses of archive management according to Muhidin and Winata, namely archive creation, archive use, archive maintenance, and archive reduction. The research approach used is descriptive qualitative with a case study method. Data collection techniques included observation, interviews, and documentation. Data analysis techniques in this study were data reduction, data presentation, and conclusion drawing. The research results indicate that: 1) The creation process is carried out fairly well, despite the limited number of staff with specialized skills in archiving; 2) Archive Maintenance is not yet functioning adequately due to the limited number of staff trained in archival management and insufficient storage space; 3) Archive Utilization can be considered adequate, though it is not yet supported by a formal written administrative system; 4) Archive Disposal has not yet reached an optimal level. Several recommendations can be considered and implemented by the Secretariat of the East Java Provincial Livestock Service: Conducting human resource training in the field of archiving, developing Standard Operating Procedures (SOPs), and implementing an e-filing system to address the limitations of physical storage space and improve efficiency in retrieving archives.